Ethnicity is important for creatinine excretion among Inuit and Caucasians in Greenland. (January 2015) - Andersen, Stig; Dehnfeld, Marie; Laurberg, Peter
Abstract Background. Human nutrition, contamination and renal function are commonly assessed by the analysis of urine. A complete 24-hour urine sample is the ideal but it is inconvenient and unreliable. Thus, spot urine sampling with creatinine adjustment is widely used. Stratification for age and gender is recommended. Still, ethnicity may influence creatinine excretion. Methods. We collected 104 24-h urine samples among Inuit and non-Inuit living in Greenland. Completeness of sampling was checked by using para-amino benzoic acid (PABA) that also allowed for compensation of creatinine excretion when sampling was incomplete. We measured creatinine using the Jaffe method and PABA by the HPLC method. Results. Participants were recruited from the capital city, a major town and a settlement (n = 36/48/20). They were aged 30–69 years with 78 Inuit and 26 non-Inuit. Inuit were smaller than non-Inuit (Caucasians): height, 163 vs. 177 cm, p < 0.001; weight, 71 vs. 84 kg, p = 0.001 with similar BMI. Creatinine excretion was lower in Inuit compared to non-Inuit (men, 1344/1807 mg/24 h; women 894/1259 mg/24 h; p = 0.002; 0.02). It was influenced by age (p < 0.001), gender (p < 0.001), weight (p = 0.001) and ethnicity (p = 0.030) while not by the intake of the protein-rich Inuit diet in the adjusted analysis. Creatinine excretion was described by: Inuit men, 1925 mg – (13.1 × age); Inuit women, 1701 mg – (17.0 × age). Conclusion. Inuit and Caucasians have different creatinine excretion. It is recommended to stratify by ethnicity in addition to adjustment for age and gender when using creatinine correction of spot urine samples.